Download presentation

Presentation is loading. Please wait.

Published byJayden Garza Modified over 2 years ago

1

2
15.3 Thermochemical Equations Pages 529 – 533

3
A. Thermochemical Equations A thermochemical equation is a balanced chemical equation that includes the physical states of all reactants and products, and energy changethermochemical equation In a thermochemical equation, the enthalpy of change for the reaction can be written as either a reactant or a product

4
A. Thermochemical Equations How to write thermochemical equations: Endothermic (positive ΔH) 2NaHCO 3 (s)+ 129kJ Na 2 CO 3 (s) + H 2 O(g) + CO 2 (g) Exothermic (negative ΔH) CaO(s) + H 2 O(l) Ca(OH) 2 (s) kJ

5
Write the thermochemical equation for the addition of oxygen gas to solid iron (III) if the ΔH rxn = kJ Fe(s) + O 2 (g) Fe 2 O 3 (s) kJ Fe(s) + O 2 (g) Fe 2 O 3 (s) kJ Write the thermochemical equation for the decomposition of sulfur trioxide gas into sulfur dioxide gas and oxygen gas if the ΔH rxn = 198 kJ SO 3 (g) kJ SO 2 (g) + O 2 (g) SO 3 (g) kJ SO 2 (g) + O 2 (g) 4 32 B. Thermochemical Equation Practice 22 Exothermic Endothermic

6
15.4 Hesss Law Pages 534 – 540

7
A. Hesss Law Hesss lawHesss law states that if you can add two or more thermochemical equations to produce a final equation for a reaction, then the sum of the enthalpy changes for the individual reactions is the enthalpy change for the final reaction Hesss law 2S(s) + 3O 2 (g) 2SO 3 (g) H = ?

8
A. Hesss Law

9
B. Hesss Law Practice Known: N 2 (g) + O 2 (g) 2NO(g) H = -180 kJ 2NO(g) + O 2 (g) 2NO 2 (g) H = -112 kJ N 2 (s) + 2O 2 (g) 2NO 2 (g) H = ? Build your equation:

10
B. Hesss Law Practice Known: 2H 2 (g) + O 2 (g) 2H 2 O(l) H = -572 kJ H 2 (g) + O 2 (g) H 2 O 2 (l) H = -188 kJ Build your equation: 2H 2 O 2 (l) 2H 2 O(l) + O 2 (g) H = ?

11
B. Hesss Law Practice Known: S(s) + O 2 (g) SO 2 (g) H = -297 kJ 2SO 3 (g) 2SO 2 (g) + O 2 (g) H = 198 kJ 2S(s) + 3O 2 (g) 2SO 3 (g) H = ? Build your equation:

12
B. Hesss Law Practice Known: 2B (s) + 3/2O 2 (g) B 2 O 3 (s) H = kJ B 2 H 6 (g) + 3O 2 (g) B 2 O 3 (s) + 3H 2 O (g) H = kJ H 2 (g) + ½ O 2 (g) H 2 O (l) H = -286 kJ H 2 O (l) H 2 O (g) H = 44 kJ 2B(s) + 3H 2 (g) B 2 H 6 (g) H = ? Build your equation:

Similar presentations

© 2016 SlidePlayer.com Inc.

All rights reserved.

Ads by Google